MEMORY CREATION IN TlInTe2-TlGdTe2 SYSTEM ALLOYS AND MECHANISMS OF OCCURRENCE OF NEGATRON EFFECTS - Ulviyye Mustafa Mustafayeva; Joshqun Jumshud. Bayramov; Khayala Vaqif Aliguliyeva; Jahangir I. Huseynov (Theoretical Hypotheses and Empirical Results, 2024)
Summary: The volt-ampere characteristics (VAC) of solid solutions of alloys of the system were studied in the direct current mode by the standard method. It has been established that there is a vast area in which there is a deviation from Ohm’s law before the start of the transformation process. In this area, the current increases exponentially depending on the voltage. In this area, the thermal effect can be neglected. An electronic conversion mechanism plays a key role here. It was found that solid solutions have a conversion property and the threshold voltage decreases with an increase in the amount of gadalinium in the composition.